Integration of Health Information Systems in Improving Emergency Management in Primary Care - Kasim, Felix (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2023)
Emergency management in primary care often faces challenges related to response speed, coordination among medical personnel, and access to accurate patient data. The integration of health information systems (HIS) is seen as a potential solution to improve the efficiency and effectiveness of emergency services.Objective: to analyze the impact of HIS implementation on emergency management in primary care and to identify the challenges in its implementation. This study employs a literature review method by collecting data from scientific journals, research reports, and relevant policy documents. Secondary data analysis was conducted to evaluate HIS implementation in various emergency cases. : The findings indicate that HIS implementation in emergencies can accelerate triage processes, enhance diagnostic accuracy, and improve coordination among medical personnel and healthcare facilities. Additionally, the system enables more optimal monitoring of medical resources. The integration of HIS in emergency management has proven to enhance the quality of services in primary healthcare facilities. However, the success of its implementation depends on the readiness of infrastructure, data protection policies, and the improvement of medical personnel's competencies in utilizing this technology